Dynamics of The Qur'an's Thematic Interpretation of Islam and Religious Plurality (Analysis of Yunahar Ilyas' Qur'anic Horizons) - Danial, Muhammad; Jannatul Husna; Waharjani (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
The religious atmosphere that tends to dominate and deny the existence of adherents of other religions is a gloomy point in the presence of a healthy religious life in the midst of pluralism, all of which are the roots of radicalism in religion. This article aims to examine the Plurality of Religions which is based on the thoughts of Yunahar Ilyas. This study is a literature review using a descriptive qualitative approach. The technique used in analyzing the data in this study is to clarify, compare and interpret the themes of Yunahar's thoughts on Islam and the Plurality of Religion with several other writings that are relevant to this research. The results of this study show that first, religious plurality as a form of life reality that Allah S.W.T. outline its whereabouts. Second, Islam views plurality as limited to the context of the reality of the existence of other religions, not at the level of faith. Third, Islamic teachings that are universal and inclusive are the basis for recognizing the existence of other religions as an effort to form good relations.